2017
DOI: 10.1017/s0950268817001716
|View full text |Cite
|
Sign up to set email alerts
|

The rise of methicillin resistantStaphylococcus aureus: now the dominant cause of skin and soft tissue infection in Central Australia

Abstract: This study aimed to examine the epidemiology and treatment outcomes of community-onset purulent staphylococcal skin and soft tissue infections (SSTI) in Central Australia. We performed a prospective observational study of patients hospitalised with community-onset purulent staphylococcal SSTI (n = 160). Indigenous patients accounted for 78% of cases. Patients were predominantly young adults; however, there were high rates of co-morbid disease. Community-associated methicillin-resistant Staphylococcus aureus (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 35 publications
2
24
0
1
Order By: Relevance
“…In previous studies and case reports, Escherichia coli infection due to skin contamination was reported to be the most common cause; however, MRSA and K. pneumoniae were detected in the abscess culture of the present patient [9]. A prospective study in Australia found that 60% of all soft tissue infections were caused by commu-nity-acquired MRSA [10]. In this patient, the mechanism causing the infection was unclear, but we assumed that infection occurred in the fat tissue because of improper storage.…”
Section: Discussionmentioning
confidence: 63%
“…In previous studies and case reports, Escherichia coli infection due to skin contamination was reported to be the most common cause; however, MRSA and K. pneumoniae were detected in the abscess culture of the present patient [9]. A prospective study in Australia found that 60% of all soft tissue infections were caused by commu-nity-acquired MRSA [10]. In this patient, the mechanism causing the infection was unclear, but we assumed that infection occurred in the fat tissue because of improper storage.…”
Section: Discussionmentioning
confidence: 63%
“…Staphylococcus aureus is a Gram-positive cocci-shaped bacterium that forms part of the normal flora on the body and is frequently isolated from the skin, respiratory tract, and female lower reproductive tract [ 11 , 12 ]. Infections by S. aureus were once treatable by penicillin.…”
Section: Microbial Biofilms and The Challenges In Infectious Diseamentioning
confidence: 99%
“…However, increasing resistance towards penicillin led to the introduction of methicillin for the treatment in 1960 [ 13 ]. However, soon after that, S. aureus acquired resistance towards methicillin, giving rise to methicillin-resistant S. aureus (MRSA) clones [ 12 , 13 ]. Currently, the Center for Disease Control (CDC) reported that infections by MRSA are the second most common cause of HAI in the USA [ 14 ].…”
Section: Microbial Biofilms and The Challenges In Infectious Diseamentioning
confidence: 99%
“…Furthermore, TMP/SMX is an important antibiotic in Australia, where community-associated methicillin-resistant Staphylococcus aureus (CA-MRSA) is common and seen more frequently in HD patients. 11 Trimethoprim/SMX resistance is presently low in Australian CA-MRSA isolates 11 but ongoing responsible antimicrobial stewardship is necessary.…”
mentioning
confidence: 99%